1986
DOI: 10.1002/mpo.2950140602
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic studies of long‐term survivors of childhood acute lymphoblastic leukemia: A follow‐up report

Abstract: Previous series including our earlier study of survivors of childhood acute lymphoblastic leukemia have documented the presence of nonclonal chromosome abnormalities in peripheral blood lymphocytes. To investigate whether or not these abnormalities persist, we restudied nine patients, all of whom had received radiotherapy and a minimum of 3 years of systemic chemotherapy. Therapy had been discontinued a median of 3.9 years prior to study in our first report and a median of 7.2 years prior to study in this foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The most obvious of these is constitutional cytogenetics of survivors, with the idea that these would reflect mutations in germline chromosomes. The results of Rubin et al [29] suggest that this is not so; the majority of survivors of childhood ALL (who do not have abnormal children) harbor a small population of longlived lymphocytes that exhibit stable nonclonal chromosomal abnormalities. Survivors of pediatric cancer have been shown to have other markers of chromosomal injury in peripheral blood, such as sister chromatid exchanges, and mutations at the glycophorin A, HGPRT, and T-cell antigen receptor loci [30][31][32].…”
Section: Future Plansmentioning
confidence: 91%
“…The most obvious of these is constitutional cytogenetics of survivors, with the idea that these would reflect mutations in germline chromosomes. The results of Rubin et al [29] suggest that this is not so; the majority of survivors of childhood ALL (who do not have abnormal children) harbor a small population of longlived lymphocytes that exhibit stable nonclonal chromosomal abnormalities. Survivors of pediatric cancer have been shown to have other markers of chromosomal injury in peripheral blood, such as sister chromatid exchanges, and mutations at the glycophorin A, HGPRT, and T-cell antigen receptor loci [30][31][32].…”
Section: Future Plansmentioning
confidence: 91%
“…The persistence of stable aberrations in peripheral blood lymphocytes following radiation exposure has long been recognised by those studying the after effects of radiotherapy, although little has been done to quantify the frequencies in relation to the time course following exposure. A G-banding study of a group of survivors of childhood leukaemia (Rubin et al 1986) reported similar overall frequencies of chromosomally aberrant cells at 3.9 and 7.2 years post-exposure but the initial yield after treatment was not examined. A group of thyroid patients displayed similar raised frequencies of translocations 1 week and 3.5 years after treatment with radioactive iodine (Puerto et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Factors reported to be associated with secondary malignancies after bone marrow transplant include the presence of acute graft vs. host disease treated with either antithymocyte globulin or an anti-CD3 monoclonal antibody, T-lymphocyte depletion of the donor, HLA mismatch between donor and recipient, and use rearrangement in the causation of secondary malignancies posttransplant; however, consistent karyotypic changes have been observed in a growing number of human malignancies (Mitelman et al, 1990), including secondary neoplasms (Arthur and Bloomfield, 1984; Le Beau et al, 1986Ratain et al, 1987Pui et al, 1989Pui et al, , 1990Albain et al, 1990;Rubin et al, 1991). Given that cells with treatment-induced chromosome abnormalities can survive for long periods (Engel et al, 1964;Visfeldt, 1966Miller et al, 1978Savage and Bigger, 1978;Mouthuy and Dutrillaux, 1982;Robison et al, 1982;Rubin et al, 1986;Zaslav et al, 1988;Barrios et al, 1989), we speculate that certain of these cells with chromosome rearrangements involving critical genes are preneoplastic and may undergo subsequent genetic changes that result in malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Ionizing radiation and many chemotherapeutic drugs are mutagenic, with the capacity to produce detectable cytogenetic alterations, and are carcinogenic in a variety of in vitro and animal test systems. Exposure of man to certain of these agents is associated with the sustained presence of hematopoietic (Miller et al, 1978Robison et al, 1982Rubin et al, 1986;Barrios et al, 1989) and nonhematopoietic (Engel et al, 1964, Visfeldt, 1966Savage andBigger, 1978 Mouthuy andDutrillaux, 1982;Zaslav et al, 1988) cells with chromosomal abnormalities and an increased risk of secondary malignancies (reviewed by Holm, 1990). It is possible that development of secondary malignancy involves therapy-induced DNA damage in the form of gene mutation or chromosome alteration resulting in conversion of a normal cell into an initiated or preneoplastic one.…”
Section: Introductionmentioning
confidence: 99%